Highly porous chitosan beads embedded with silver-graphene oxide nanocomposites for antibacterial application - Soon, Wei Chook; Chin, Hua Chia; Hatika Kaco,; Sarani Zakaria,; Nay, Ming Huang; Hui, Min Neoh (Universiti Kebangsaan Malaysia, 2016)
Incorporation of silver nanomaterial into polymer matrix can further accomplished their potential usage in real life applications. In our previous study, silver nanoparticles (AgNPs) and silver-graphene oxide nanocomposites (AgGO) were prepared via a rapid microwave-assisted method. Hereby, the as-synthesized AgNPs or AgGO was dispersed in a chitosan solution. Subsequently, the resultant mixture solution was further coagulated in a coagulation bath containing sodium hydroxide via a neutralization process. This resulted in the formation of spherical-shaped chitosan beads. The structure of the beads showed that the chitosan beads embedded with AgGO exhibited a more porous structure as compared to the plain chitosan beads. Furthermore, the chitosan beads containing AgNPs or AgGO were tested for their antibacterial activity against Escherichia coli and Staphylococcus aureus. The antibacterial results indicated that the silver nanomaterial contained chitosan beads could effectively inhibit the growth of both E. coli and S. aureus as compared to the bare chitosan beads. The produced chitosan nanocomposite envisioned that can be potentially employed for water disinfection purpose.